2017
DOI: 10.1103/physrevd.95.076009
|View full text |Cite
|
Sign up to set email alerts
|

Superscaling analysis of quasielastic electron scattering with relativistic effective mass

Abstract: We provide a parametrization of a new phenomenological scaling function obtained from a chisquare fit to a selected set of (e,e') cross section data expanding a band centered around the quasielastic peak. We start from a re-analysis of quasielastic electron scattering from nuclear matter within the relativistic mean field model. The cross section depends on the relativistic effective mass of the nucleon, m * N , and it scales with respect to a new scaling variable, ψ * . This suggests a new superscaling approa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…We carried out such analyses in Refs. [43][44][45][46]. In the SuSAM* models, the response functions are computed by using Eq.…”
Section: Scaling Analysis Of Subtracted Datamentioning
confidence: 99%
See 4 more Smart Citations
“…We carried out such analyses in Refs. [43][44][45][46]. In the SuSAM* models, the response functions are computed by using Eq.…”
Section: Scaling Analysis Of Subtracted Datamentioning
confidence: 99%
“…4, we plot f * versus ψ * for all the data of 12 C. The values of M * = 0.8 and Fermi momentum k F = 225 MeV/c have been taken from the previous analyses of Refs. [43][44][45][46], where it was shown that these values provide the best scaling of data. In Fig.…”
Section: Scaling Analysis Of Subtracted Datamentioning
confidence: 99%
See 3 more Smart Citations